CONCEPTUAL DESIGN AND ANALYSIS OF SMALL LONG-LIFE PRESSURIZED WATER REACTOR (PWR) USING THORIUM CYCLE - NURUL SUBKHI (NIM : 30211007), MOH.
Long-life reactor is a nuclear power plant which can be operated 10-30 years of operation without the need for refueling or fuel shuffling. Such nuclear power plant is very good to supply electricity in remote area in Indonesia and in general outside Java Bali Area. Here, a conceptual design study of small long-life Pressurized Water Reactor using thorium cycle has been performed in neutronic aspect. Thorium cycle which has higher conversion ratio produces some significant of 233U during burnup time. The strategy of moderator reduction is by adopting tight lattice model based on square and hexagonal geometry cell and by the use of 231Pa as burnable poison material which gives good long-life core during burnup time. Such burnable poison has very large capture cross section that can reduce reactivity in the beginning of life.The cell calculations were performed by PIJ SRAC code using nuclear data library based on JENDL 3.2/3.3, while the core burnup calculations were optimized in whole X-Y-Z geometry by COREBN. The neutronic analysis result of infinite cell calculation shows that mixed nitride with ZIRLO as cladding is better than oxide and carbide in thorium fuel system. In the present study, we consider thorium nitride system with 3 ~ 8 % 233U percentage and 0.2 ~ 7% 231Pa as fuel for small PWR and can be burnup for the long-time. The purpose of the study is to optimize the design of 100-600 MWt PWR which can be operated without refueling in more than 10 years. A small long-life fuel with the thorium nitride fuel system in square and hexagonal cell geometry is introduced with fuel fraction 60%. By using this concept, small PWR (125 cm x 285 cm) can be designed for long time operation with reduced excess reactivity as low as 1.2 dk/k for homogenous core. Finally, the optimization of 350 MWt small long-life PWR based on thorium nitride fuel system has been done in heterogenous core and it has excess reactivity as low as about 0.9% dk/k with flatted power distribution during its operation.